1972
DOI: 10.1161/01.cir.45.5.1018
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmias following Cardiac Valve Replacement

Abstract: A prospective study of 50 consecutive patients undergoing cardiac valve replacement was designed to determine the incidence, types, and predisposing factors to postoperative arrhythmias. Patients were monitored continuously for the first 7 days following surgery. Thirty-seven patients (74%) experienced a total of 66 episodes of arrhythmia. Supra-ventricualr arrhythmias were the most common (43 of 66; 65%). The most frequent specific arrhythmia was atrial fibrillation (21 of 66; 32%). Arrhythmias occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The incidence of AF in hospitalized patients was reported to be 24% by Goldman 13. Smith et al14 and Stephenson et al15 reported an AF incidence rate of 10% after cardiac valve surgery and open heart surgery. The highest incidence reported was 65% by Mathew et al16 but the incidence of AF after coronary artery bypass graft surgery is much lower, ranging from 3.3% to 30% 16,17.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of AF in hospitalized patients was reported to be 24% by Goldman 13. Smith et al14 and Stephenson et al15 reported an AF incidence rate of 10% after cardiac valve surgery and open heart surgery. The highest incidence reported was 65% by Mathew et al16 but the incidence of AF after coronary artery bypass graft surgery is much lower, ranging from 3.3% to 30% 16,17.…”
Section: Resultsmentioning
confidence: 99%
“…Our methods did not permit us to establish the incidence of VA following AVI. Limited data concerning acute postoperative VA reports a varied incidence ranging from 0.74% to 21% 5,6 . Yet, VA can present years following surgical intervention, akin to postoperative atrial arrhythmias and post‐myocardial infarction VA 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Limited data concerning acute postoperative VA reports a varied incidence ranging from 0.74% to 21%. 5,6 Yet, VA can present years following surgical intervention, akin to postoperative atrial arrhythmias and postmyocardial infarction VA. 2 indeed, the difference in VA timing related to valve surgery may be due to variation in the arrhythmia mechanism.…”
Section: Follow-up After Va Ablationmentioning
confidence: 99%
“…Though this study included 749 patients with MVS, the incidence of VT was reported after valve surgery in general. Another study reported that the incidence of VT was 8% in patients with mitral valve replacement compared to 21% with aortic valve replacement 23 . Though these studies evaluated acute incidence, VA can present years following surgical intervention, akin to postoperative atrial flutter and post myocardial infarction ventricular arrhythmias 10 .…”
Section: Discussionmentioning
confidence: 99%